Improved ultrastructure of marine invertebrates using non-toxic buffers - Jacqueline Montanaro; Daniela Gruber; Nikolaus Leisch (PeerJ, 2016)
Many marine biology studies depend on field work on ships or remote sampling locations where sophisticated sample preservation techniques (e.g., high-pressure freezing) are often limited or unavailable. Our aim was to optimize the ultrastructural preservation of marine invertebrates, especially when working in the field. To achieve chemically-fixed material of the highest quality, we compared the resulting ultrastructure of gill tissue of the mussel Mytilus edulis when fixed with differently buffered EM fixatives for marine specimens (seawater, cacodylate and phosphate buffer) and a new fixative formulation with the non-toxic PHEM buffer (PIPES, HEPES, EGTA and MgCl2). All buffers were adapted for immersion fixation to form an isotonic fixative in combination with 2.5% glutaraldehyde. We showed that PHEM buffer based fixatives resulted in equal or better ultrastructure preservation when directly compared to routine standard fixatives. These results were also reproducible when extending the PHEM buffered fixative to the fixation of additional different marine invertebrate species, which also displayed excellent ultrastructural detail. We highly recommend the usage of PHEM-buffered fixation for the fixation of marine invertebrates.